The association between the weight-adjusted-waist index and frailty in US older adults: a cross-sectional study of NHANES 2007–2018 - Jia, Shanshan; Huo, Xingwei; Sun, Lirong; Yao, Yuanyuan; Chen, Xiaoping (Frontiers in Endocrinology, 2024)
Objective: This study aimed to evaluate the relationship between the weight-adjusted waist circumference index (WWI) and the frailty in American adults aged over 60 years. Methods: We utilized data from the National Health and Nutrition Examination Surveys (NHANES) spanning from 2007 to 2018. WWI was calculated using the square root of waist circumference (cm) divided by body weight (kg). The frailty index ≥ 0.25 was employed to assess frailty. Weighted multivariate logistic regression was conducted to explore the association between WWI and frailty. Generalized Additive Modeling (GAM) was used to explore potential non-linear relationships. Receiver operating characteristic curve (ROC) analysis was used to assess the predictive ability of WWI for frailty.The study encompassed 7765 8550 participants. Higher WWI was significantly associated with lower odds of frailty. In the fully adjusted model, each unit increase of WWI was associated with an 82% increased odds of frailty (OR: 1.82, 95% CI: 1.61 -2.06; P < 0.001). In the fully adjusted model, each unit increase of WWI was associated with 64% increased odds of frailty (OR: 1.64, 95% CI: 1.48 -1.82; P < 0.001). GAM found significant nonlinear relationships and threshold effects.The study presented a robust correlation between elevated WWI and increased odds of frailty among American older adults. However, these findings require further validation in large-scale, prospective studies.